Biportal transparotid dissection in the retromandibular approach for condylar fracture osteosynthesis: Efficacy of a novel technique. Issue 5 (May 2020) - Abdelwahab, Mohamed A.; Spataro, Emily A.; Elkholy, Noha A.; El-Degwi, Ahmed; Most, Sam P.
Summary: Objective: Facial nerve injury is a primary complication of open surgical management of condylar fractures. A new modification of the retromandibular transparotid approach, the "biportal transparotid dissection" (BTD), was developed to reduce these injuries in accidental nerve exposure. Design: Prospective cohort study. Setting: Tertiary referral center. Methods: Patients managed by retromandibular transparotid approach for condylar fractures at Department of Otolaryngology – Head and Neck Surgery, Mansoura University were included between November 2015 and August 2019 with exclusion of cases managed endoscopically or by a closed approach. Three groups were identified: Group A included patients undergoing the BTD technique, which entails transparotid dissection above and below exposed nerve branches and minimal nerve retraction; Group B included patients undergoing traditional dissection and nerve retraction away from the surgical field; and Group C included patients with unidentified facial nerve branches. The function of facial nerve branches was documented postoperatively. Results: Fifty-seven fractures were included in the study. Facial nerve branches' injury occurred in 13 cases (22.8%): two (of ten) in Group A (20%), seven (of ten) in Group B (70%) and four (of 37) in Group C (10.81%). Compared to patients with non-exposed branches, Groups A and B were found to have 2.06 ( p  = 0.447) and 19.25 ( p  = 0.001) greater odds of nerve injury, respectively. The results showed significant faster nerve recovery in the BTD group compared to traditional dissection (mean 5 versus 9 weeks) ( p  = 0.015). Conclusion and relevance: Although avoiding facial nerve exposure minimizes injury the most, BTD approach reduces exposed nerve injury compared to the traditional method.